Dynamic template directed construction of three-dimensional porous bismuth aerogels for high-rate Na-ion storage. Issue 11 (1st March 2023) - Liu, Yani; Wang, Yu; Wang, Haoqiang; Dou, Shuming; Tian, Huijie; Gan, Wei; Yuan, Qunhui
Abstract : A carbon-free 3D porous metallic Bi aerogel anode for high-rate Na-ion storage was fabricated through a simple dynamic template strategy, showing excellent capability for rapid ion/electron transfer and volume fluctuation. Abstract : Aiming to achieve a metallic bismuth (Bi) anode with constant accommodation of volume change, a dynamic template strategy is proposed for fabrication of a highly adjustable Bi aerogel anode. In the presence of the NaBH4 reductant, the in situ generated hydrogen bubbles served as dynamic templates to direct the reduction, nucleation and growth of Bi nanoparticles, which are subsequently merged into a three-dimensional porous skeleton. The unique 3D porous Bi skeleton ensures the rapid alloying/dealloying of sodium ions and efficient electrolyte infiltration. Its excellent structural integrity and buffering capacity for volume fluctuation lead to superior rate performance (330.6 mA h g −1 at 30C) and long-term stability (339.1 mA h g −1 after 2000 cycles at 10C) in a half cell. When coupled with a Na3 V2 (PO4 )3 cathode, the Na3 V2 (PO4 )3 //Bi full cell exhibits appealing energy density and power density. This work demonstrates a new idea for constructing highly reliable alloy-type anodes for high-rate energy storage systems.